“La disortografía en el proceso de enseñanza aprendizaje” - Caizalitin Tercero, Jenifer Jimena (2023)
In the educational process, students go through several stages until they reach the orthographic sign, where they assimilate that writing has diverse rules, which must be taken into account to the moment makes a writing, however, spelling errors are a problem, which have affected to global level. The aim was to identify the dysorthography incide in the teaching-learning process of seventh grade students from EGB parallel "A" from "14 de Octubre - Vicente Rocafuerte" Educational Unit. The used methodology was based on focused qualitative research on the interpretative paradigm, what intends to describe, analyze and interpret reality. Faced with this, it has been necessary to apply documentary or bibliographic and field research, accompanied by the inductive method, same, what starts from the particular to the general. Finally, it was applied the interview technique with the respective instrument, which allowed the relevant information collection for the research results analysis and formulation. It was determined, what disorthography affects the words correct spelling and spelling rules aplication, which generates a communication deficit at a social, technological and academic level, what prevents understanding the written text. The research helped to know the dysorthography level in the children to analyze the performance in the language and literature area and thus it can contribute to the didactic process. It is recommended, what teachers apply strategies, which help improve spelling and their school performance.